Severe Airway Injury Due to Alendronate Aspiration. Issue 6 (2013) - MacEachern, Paul; Brazil, Aiden; Tremblay, Alain; Stather, David R; Chee, Alex C; Chou, Julie
Abstract : Sequelae of foreign body aspiration can range from clinically silent and asymptomatic to immediate asphyxiation and death. Only two previous cases of bisphosphonate tablet aspiration have been reported. Ulcerative esophagitis, a known adverse effect of oral bisphosphonate formulations, occurs primarily with prolonged exposure of esophageal mucosa to the medication. Little is known about the effects of bisphosphonates on the airway mucosa. The authors present a case involving an 84-year-old woman who required multiple bronchoscopic debridements, intubation for airway protection and intensive care unit admission following airway injury believed to be due to delayed recognition of aspiration of an alendronate tablet.